Penal Code (Amendment) Act 1989 - Kamariah, Mimi (Journal of Malaysian and Comparative Law, 2019)
The Penal Code (Amendment) Act 1989 came into force on the 5th of May 1989. The main aims of the amendment were to improve and lighten the definitions for several sexual offences, such as rape, carnal intercourse and buggery with an animal, and to increase the punishments for sexual offences and offences against property. The amendment aso covers the offence of causing miscarriage and offences related to obscene articles or objects.